ALAT TES KETERAMPILAN SEPAK TAKRAW BAGI ATLET SEPAK TAKRAW JAWA TENGAH - Sulaiman (Universitas Negeri Semarang, 2014)
This study aims to develop a test instrument for sepak takraw skill for males and females athletes of Central Java. This research method is a survey with tests and measurements. Research sample is 46 males athletes and 35 females athletes of Sepak Takraw in Central Java. Test of skills consist of four test items: 1) test of sepak mula ability, 2) test of sepak kura ability, 3) feed tests, and 4) test of smash ability. The instrument of test is tested by Chi square statistics, validity with statistical tests of Pearson Product moment to correlate the test items for the total score, reliability tested in two ways. Product moment to correlate the total score of the first test with a total score of the second test, and with Anava two lines to test the homogeneity of variance. Conclusions The results of research is, test of sepak takraws skill can be used as an instrument to measure the skills of males and females athletes of sepak takraw In Central Java